2020
DOI: 10.1002/cbf.3537
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid triggers apoptosis and inhibits migration and invasion of gastric cancer cells by impairing EMT progress

Abstract: Gastric cancer (GC) is one of the most prevalent types of malignancies. Betulinic acid (BA) is a natural pentacyclic triterpene with a lupine structure. However, to the best of our knowledge, there is no research study on the anti-tumour and anti-metastasis effect of BA on GC. In this study, we assessed the anti-cancer effect of BA on human GC cells in vitro and in vivo. We first investigated the cytotoxicity and antiproliferation effect of BA on GC cells of SNU-16 and NCI-N87. The results indicated that BA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…68 Betulinic acid, a naturally occurring pentacyclic triterpenoid with a lupine structure, and normally found in the bark of birch trees, evidently inhibits the epithelial–mesenchymal transition signaling pathway to block gastric cancer cell migration and invasion in vivo and in vitro . 69…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…68 Betulinic acid, a naturally occurring pentacyclic triterpenoid with a lupine structure, and normally found in the bark of birch trees, evidently inhibits the epithelial–mesenchymal transition signaling pathway to block gastric cancer cell migration and invasion in vivo and in vitro . 69…”
Section: Phytochemicals For Cancer Prevention and Therapymentioning
confidence: 99%
“…BA could significantly suppress activity of EMT by upregulating epithelial protein and downregulating mesenchymal protein simultaneously. Previous study demonstrated that BA triggers apoptosis and inhibits migration and invasion of gastric cancer cells by impairing EMT progress (Chen et al., 2020). Sun et al showed that BA can inhibit stemness and EMT of pancreatic cancer cells via activation of AMPK signaling (Sun et al., 2019).…”
Section: Discussionmentioning
confidence: 97%
“…BA could also downregulate expression of MMP2 and MMP9, resulting in a suppression of tumor cells migration and invasion (Wang et al., 2019; Yang, Li, Fu, Jiang, & Meng, 2018; Zeng et al., 2018). It is reported that BA could suppress breast cancer cell migration and invasion by impairing epithelial‐mesenchymal transition (EMT) (Chen, Wu, Liu, & Zhou, 2020). The BA has gradually become one of the hot spots in the research of anticancer drug compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer, metabolomics have revealed the mechanisms underlying novel cancer treatments using Chinese herbal medicines. Yang et al used an UPLC-MS/MS assay to identify that shikonin could inhibit CRC cell growth via various signaling pathways that included glutathione metabolism, arginine biosynthesis, purine metabolism, betaalanine metabolism, and arginine biosynthesis (Chen et al, 2020b). Daddiouaissa et al (2021)performed metabolic profiling and utilized multivariate data analysis combined with an ingenuity pathway analysis (IPA) to explore the effects of treating CRC cells with the ionic liquid-Graviola fruit pulp extract (IL-GPE).…”
Section: Metabolomicsmentioning
confidence: 99%